Resectional One Anastomosis Gastric Bypass/Mini Gastric Bypass as a Novel Option for Revision of Restrictive Procedures: Preliminary Results - Roger Noun; Rita Slim; Ghassan Chakhtoura; Joseph Gharios; Elie Chouillard; Carla Tohmé-Noun (Journal of Obesity, 2018)
Background. Revisional surgery is becoming a common and challenging practice in bariatric centers. The aim of this study was to evaluate resectional one anastomosis gastric bypass/mini gastric bypass (R-OAGB/MGB) as a revisional procedure. Methods. From January 2016 to February 2017, data on 21 consecutive patients undergoing R-OAGB/MGB for weight loss failure after primary restrictive procedures were prospectively collected and analysed. Results. Mean age was 39 ± 12 years (18–65), and 11 (52.3%) were women. The mean operative time was 96.4 ± 20.9 min (range, 122–80), and the mean postoperative stay was 47.8 ± 7.4 hours (range, 36–73). There were no deaths and no procedure-related complications. The mean body mass index (BMI) decreased from 42.9 ± 6.5 at the time of R-OAGB/MGB to 28.5 ± 4 at the 12-month follow-up. At that time point, the mean percentage of BMI loss (%EBL) and the mean percentage of total body weight loss (%TWL) reached 81.6 ± 0.17% and 35 ± 0.01%, respectively. Conclusion. R-OAGB/MGB was technically straightforward, effective, and safe in this at-surgical risk population. R-OAGB/MGB should be added to the armamentarium of revisional bariatric procedures considering its technical aspects and the potential advantage on weight loss.